Disposisi Matematis Mahasiswa dalam Pembelajaran Matematika dengan Metode Socrates - Betti Dian Wahyuni; Moch Iqbal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to describe the mathematical disposition of students in learning using the Socratic method. This research is a qualitative descriptive study. The research subjects were students of Tadris Mathematics IAIN Bengkulu Semester IIA. The subjects of this study were selected through techniques. Purposive sampling qualitative data of students' mathematical dispositions were obtained through observation, documentation, questionnaires, and interviews. Before analyzing the data, the researcher triangulated the data sources. The data analysis technique of this research went through 3 stages, namely reduction, presentation, and drawing conclusions on the data. The results of the research, from the calculation of the students' mathematical disposition scale questionnaire were classified into two categories, namely high mathematical disposition and medium mathematical disposition. During the process of learning mathematics using the Socratic method, all indicators of mathematical disposition were manifested by students with a high mathematical disposition classification, including: self-confidence, interest and curiosity, perseverance, and flexibility. Meanwhile, for students with moderate mathematical disposition classification, the tendency that appears is an indicator of flexibility, while for other indicators the dominance of the emergence is different. In conclusion, students' mathematical dispositions in learning using the Socratic method can be classified into two categories of dispositions, namely high mathematical dispositions and moderate mathematical dispositions. Keywords: Mathematical Disposition, Socratic Method, Mathematics Learning